The Journey Ahead: Thirteen Teachers Report How the Internet Influences Literacy and Literacy Instruction in Their K-12 Classrooms - Karchmer, Rachel A. (Reading research quarterly, 2001)
The purpose of this study was to explore 13 K-12 teachers' reports of how the Internet influenced literacy and literacy instruction in their classrooms. The teachers, including ten women and three men, represented 11 different states in the U. S. and were considered exemplary at using technology by their colleagues. Labbo and Reinking's (1999) notion of multiple realities in relation to new technologies provided a framework for understanding the participants' perspectives of the Internet's relationship to literacy and literacy instruction. Constant-comparative analysis of data, including e-mail interviews, participants' reflective journals, Web pages, online articles, and lesson plans revealed three areas of focus: (a) the appropriateness of Internet material, (b) evaluating the accuracy of Internet material, and (c) publishing student work on the Internet. Findings indicated that the teachers viewed the Internet's influence on reading as an extension of traditional literacy skills. In addition, the elementary teachers noticed an increase in their students' motivation to write when their work was published on the Internet for a greater audience. However, the secondary teachers did not find this the case. Implications for teacher technology preparation and literacy research are discussed in light of the lessons learned from this study. /// [Spanish] El propósito de este estudio fue explorar los informes de 13 docentes K-12 acerca de cómo la Internet influenció la alfabetización y la enseñanza de la lectoescritura en sus aulas. Los docentes, diez mujeres y tres hombres, representaban 11 estados diferentes de los Estados Unidos y eran considerados por sus colegas un ejemplo en el uso de la tecnología. La noción de realidades múltiples en relación con las nuevas tecnologías formulada por Labbo y Reinking (1999) proporcionó un marco para comprender las perspectivas de los participantes sobre la relación entre la Internet y la alfabetización y la enseñanza de la lectoescritura. Análisis comparativos de datos que incluyeron entrevistas por correo electrónico, diarios de reflexiones de los participantes, páginas de la red, artículos on-line y planificaciones de clases revelaron tres áreas de interés: (a) adecuación del material de la Internet, (b) evaluación de la precisión del material de la Internet y (c) publicación del trabajo de los estudiantes en la Internet. Los resultados indicaron que los docentes veían la influencia de la Internet sobre la lectura como una extensión de las habilidades tradicionales de lectoescritura. Asimismo, los docentes primarios percibieron un aumento en la motivación de los estudiantes para escribir cuando su trabajo se publicaba en la Internet para una audiencia mayor. Sin embargo, los docentes secundarios no hallaron esto. Se discuten las implicancias para la capacitación tecnológica de los docentes y la investigación en alfabetización a la luz de lo aprendido a partir de este estudio. /// [German] Zweck dieser Studie war das Auswerten von 13 K-12 Lehrerberichten darüber, wie das Internet den Schreib- und Leseunterricht in ihren Klassenräumen beeinflußt. Die Lehrer, einschließlich zehn Frauen und drei Männern, repräsentierten 11 verschiedene Staaten in den USA und galten bei ihren Kollegen als beispielhaft in der Technologienutzung. Der Begriff der multiplen Realitäten in Relation zu neuen Technologien von Labbo und Reinking (1999) lieferte einen Rahmen zum Verständnis der Teilnehmerperspektiven in Verbindung zum Schreiben und Lesen und Schreib- und Leseuterricht des Internet. Die konstant-komparative Analyse der Daten, einschließlich Email Interviews, reflektive Journale von Teilnehmern, Webseiten, On-Line Artikel, und Unterrichtspläne ergaben drei Brennpunktbereiche: (a) Die Zweckmäßigkeit bzw. Angemessenheit von Internetmaterial, (b) Bewertung der Genauigkeit von Internetmaterial, und (c) Veröffentlichen von Schülerarbeiten im Internet. Die Erkenntnisse weisen daraufhin, daß die Lehrer den Einfluß des Internet auf das Lesen als eine Ergänzung traditioneller Schreib- und Lesefertigkeiten ansahen. Zusätzlich erkannten die Grundschullehrer eine Steigerung in der Motivation ihrer Schüler zum Schreiben, wenn ihre Arbeiten im Internet für ein größeres Publikum veröffentlicht wurden. Die Oberschullehrer stellten dies jedoch nicht fest. Auswirkungen auf die Technologievorbereitung und Schreib- und Leseforschung für Lehrer werden im Hinblick auf die aus dieser Studie gemachten Erfahrungen diskutiert. /// [French] Cette étude avait pour but d'explorer les rapports de 13 enseignants, du jardin d'enfants au baccalauréat, sur la façon dont internet affecte la littératie et l'enseignement de la littératie dans leur classe. Ces enseignants, dix femmes et trois hommes, représentent 11 États différents des USA et sont considérés comme exemplaires par leurs collègues en ce qui concerne l'utilisation de la technologie. La notion de réalités multiples en rapport avec les nouvelles technologies de Labbo et Reinking (1999) a fourni une structure pour comprendre les perspectives des participants en ce qui concerne la relation d'internet à la littératie et à l'enseignement de la littératie. Une analyse comparative commune des données, comportant des entretiens par e-mail, des journaux de réflexion des participants, des pages web, des articles en ligne, et des plans de cours, ont fait apparaître trois domaines de préoccupation: a) la pertinence du matériel d'internet, b) l'évaluation de la précision du matériel d'internet, et c) la publication du travail des élèves sur internet. Les résultats indiquent que les enseignants considèrent l'influence d'internet sur la lecture comme une extension des compétences traditionnelles de littératie. De plus, les enseignants du primaire remarquent une augmentation de la motivation de leurs étudiants à écrire quand leur travail est publié sur internet à destination d'un plus grand public. Cependant, les professeurs du second degré ne trouvent que ce soit le cas. À la lumière des leçons tirées de cette étude, la discussion porte sur les implications pour la formation technologique des enseignants et sur la recherche en littératie. /// [Cyrillic] В задачи данного исследования входило изучение мнений тринадцати учителей, работающих с детьми различных возрастов, о влиянии Интернета на чтение учащихся и обучение литературе. Коллеги считают, что эти учителя (десять женщин и трое мужчин, представляющие 11 американских штатов) преуспели в использовании компьютерных технологий при обучении. Положение о возникновении множественных реалий благодаря новым технологиям (Лаббо и Рейнкинг, 1999) помогает понять, под каким углом зрения участники опроса рассматривают влияние Интеренета на чтение и преподавание литературы. Постоянно-сравнительный анализ данных, в том числе: интервью, полученных посредством электронной почты; дневниковых записей участников; веб-страниц; статей в режиме онлайн и планов уроков -- дал возможность выделить три аспекта, представляющие особый интерес, (а) уместность применения Интернет-материалов, (б) оценка точности материалов, представленных в Интернете и (в) публикация ученических работ в Интеренете. Как выяснилось, учителя считают, что Интернет расширяет традиционные навыки общения с печатным словом. Кроме того, учителя начальной школы -- в отличие от средней -- отмечают, что дети охотнее пишут, зная, что их произведения обретут широкую аудиторию на страницах Интернета. В свете полученных данных обсуждается необходимость технологической подготовки учителей и проведения смежных исследований в области чтения и письма.